2020
DOI: 10.3390/insects11070414
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Interaction between Aphis spiraecola and Toxoptera citricida on Sweet Orange Induced by Pre-Infestation

Abstract: Indirect interactions between herbivorous insects that share the same host have been focused on insects feeding on herbaceous plants, while few studies investigate similar interactions on woody plants. We investigated performance and feeding behavior of two citrus aphids, Aphis spiraecola Patch and Toxoptera citricida Kirkaldy, on sweet orange as affected by prior infestation of conspecifics and heterospecifics. Results showed that pre-infestation-induced interactions between A. spiraecola and T. citri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Previously, we found that A. spiraecola infestation induced phytohormone-based SA and JA signaling defenses, whereas A. citricidus did not affect SA and inhibited JA signaling (Gao et al, 2020), implying that A. spiraecola may encounter more difficulty in ingesting plant nutrients than A. citricidus. However, how the plant defenses induced by citrus aphids change during infestation is unknown.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Previously, we found that A. spiraecola infestation induced phytohormone-based SA and JA signaling defenses, whereas A. citricidus did not affect SA and inhibited JA signaling (Gao et al, 2020), implying that A. spiraecola may encounter more difficulty in ingesting plant nutrients than A. citricidus. However, how the plant defenses induced by citrus aphids change during infestation is unknown.…”
Section: Introductionmentioning
confidence: 82%
“…Second, leaf curling may provide a sheltered micro-environment that protects A. spiraecola from natural enemies and other threats (Goggin, 2007). Third, the plant-mediated indirect interaction between the two citrus aphids favors A. spiraecola as a superior competitor (Gao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a reduced phloem sap ingestion duration was observed on D. citri feeding on citrus plants drenched with the insecticides thiamethoxam and imidacloprid [ 26 ]. Previously, the duration of phloem sap was linked to the performance of piercing–sucking insects [ 30 , 31 , 32 ]. Therefore, our findings help to explain the negative effect of vermicompost on piercing–sucking insects from the aspect of feeding behavior.…”
Section: Discussionmentioning
confidence: 99%